Film-induced pilgrimage and contested heritage space in Taipei City. (June 2017) - Chen, Fuwei; Mele, Christopher
Abstract: This article examines the effects of film-induced pilgrimages on a specific, often contested aspect of urban place production – the designation of heritage space, a process rooted in the local landscape, architecture, people, artifacts, traditions and stories that render a location culturally and historically significant. In particular, this article examines how film-induced pilgrimages create destination places which, in turn, influence and alter longstanding political struggles over heritage meaning among local residents, preservationists and government agencies. The effect of unanticipated cultural forces, such as film-induced pilgrimages, is rarely politically impartial; rather, a place's destination status may be used and responded to strategically by local stakeholders in support of their conflicting claims over heritage production. Highlights: Film-induced pilgrimage acts as a contingent and unanticipated cultural force that influences the political struggles over the public meaning of heritage. The cultural status of a place as a film-induced popular destination may used by local stakeholders to strategically promote contested claims over heritage place identity. The article provides a case study of heritage and preservation of Bopiliao in Taipei, Taiwan, which emerged as a popular destination for fans of 2010 hit film, Monga .